2018
DOI: 10.1002/aenm.201802674
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Air‐Stable Aqueous‐Processed Organic Solar Cells and Transistors: Impact of Water Addition on Processability and Thin‐Film Morphologies of Electroactive Materials

Abstract: transistors (OFETs), organic light emitting diodes and polymer solar cells (PSCs), developing ecofriendly processing methods suitable for industrial fabrication has become an important topic of recent investigations. [1,2] To this end, a great deal of research efforts have been devoted to phasing out halogenated solvents such as chloroform and chlorobenzene, which have been prevalent for optimizing the fabrication of lab-scale OFET and PSC devices, because they are detrimental to both human health and the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 68 publications
(101 reference statements)
0
58
0
Order By: Relevance
“…Recent studies demonstrated that replacing alkyls with oligo(ethylene glycol) side chains is able to generate water or alcohol soluble conjugated polymers and acceptors. [184][185][186][187] In addition, scalable coating methods such as blade coating, [188][189][190][191][192] and slot-die coating [193][194][195][196][197] and roll-to-roll printing [198,199] should be more extensively explored. 6) Development of PT-based all-polymer solar cells: All-polymer solar cells exhibit unique advantages, such as excellent mechanical property, good morphological stability, and readily tunable solution viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that replacing alkyls with oligo(ethylene glycol) side chains is able to generate water or alcohol soluble conjugated polymers and acceptors. [184][185][186][187] In addition, scalable coating methods such as blade coating, [188][189][190][191][192] and slot-die coating [193][194][195][196][197] and roll-to-roll printing [198,199] should be more extensively explored. 6) Development of PT-based all-polymer solar cells: All-polymer solar cells exhibit unique advantages, such as excellent mechanical property, good morphological stability, and readily tunable solution viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Originally, alkyl side chains were introduced to aid solubility and, generally, processability; 11 while more recently polar side chains, such as those based on oligo(ethylene oxide) groups, have attracted interest as they render the base material more compatible with socalled 'green' solvents. 12,13 Moreover, polymer semiconductors, substituted with polar side chains, are interesting for bioelectronic applications, for instance, where mixed electron/ion conduction is required (e.g., in electrochemical transistors used for biomimetic signal transduction, ion pumps, bioactive sensing elements), or where high biocompatibility is needed, including biointegrated electronics and wearable devices. [14][15][16][17][18][19] However, side chains can inhibit backbone packing and aggregation, and often introduce undesired torsional backbone disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic conjugated molecular materials have become a research hotspot in the field of photoelectric molecular materials because of their wide application in photoluminescence [3][4][5], photoelectric devices [6,7], field effect transistors [8,9] and functional complexes [10]. 1,8-Naphthalimide derivatives are important organic conjugated molecules which can be used as fluorophores in the design of fluorescent probe [11] and prodrug [12].…”
Section: Commentmentioning
confidence: 99%